BUSINESS SUSTAINABILITY MODEL IN THE NEW NORMAL ERA THROUGH MICRO AND SMALL BUSINESS DIGITAL PLATFORMS IN RURAL AREAS - Bayu, Kartib (Archives of Business Research, 2021)
The policy of preventing the transmission of Covid-19 through Large-Scale Social Borders and the Enforcement of Restrictions on Community Activities has had an impact on the economy. Many micro and small businesses have stopped operating, workers have been laid off, unemployment has increased, and there has been new poverty. This study aims to implement a business sustainability model that can adapt to new normal conditions supported by digital platform applications in a rural area and obtain a Covid-19 prevention model with a change in business governance orientation approach that can adapt to the new normal era. The research method used is literature study, exploratory survey, experimental research, and applied research. A field survey was conducted to obtain primary data at the village level. An experimental method to test business sustainability models and digital platform applications on micro and small businesses. Digital platform literacy is carried out through online workshops. The unit of analysis is micro and small business actors. The data analyzed are time series. The research site was in Sumedang Regency from September 2020 to July 2021. The results showed that during the Covid-19 pandemic there were micro and small business activities that made changes, although there were also those who laid off their businesses. Adjustments in the form of substitution of raw materials, modification, diversification, making new products, and changing the way of marketing. The digital platform design is made on a web and android based to carry out the function or process of online transactions for micro and small business products in rural areas. It is hoped that MSE entrepreneurs will understand, through complete information, adjusting needs, as well as helping prevent the transmission of Covid-19 and can support business sustainability in the new normal era.